Frontispiece: Origin of the Photoinduced Geometrical Change of Copper(I) Complexes from the Quantum Chemical Topology View. Issue 3 (15th January 2019) - Gutiérrez‐Arzaluz, Luis; Ramírez‐Palma, David Ignacio; Ramírez‐Palma, Lillian G.; Barquera‐Lozada, José Enrique; Peon, Jorge; Cortés‐Guzmán, Fernando
Abstract : An alternative explanation for the photoinduced structural change of copper(I) complexes, based on the electron density redistribution, is described. The electronic excitation produces a metal‐to‐ligand charge transfer that destabilizes the metal center due to the decrease of the nuclear‐electron interactions. To counterbalance the copper destabilization, the metal valence shell polarizes during the deactivation path to increase the magnitude of the intra‐metal nuclear‐electron interactions, which provokes the flattening of the structure to obtain the geometry with the maximum interaction between the charge depletions of the metal with the charge concentrations of the ligand. For more information, see the Full Paper by F. Cortés‐Guzmán et al. on page 775 ff.